Negus Ezana: Revisiting the Christianisation of Aksum - Rukuni, Rugare (Verbum et ecclesia, 2021)
The Christianisation of Ethiopia is decoded within the reign of Ezana. The person of Ezana as a real-time figure and within the context of then Aksumite religious-cultural and political dynamics creates the background of the narrative for Ethiopian Christianity. In a revised study as a follow-up to the investigations of the dating of Ezana, revisiting his conversion, the study attempts to locate the Negus within the complex of then emergent Christian orthodoxy continuum whilst assigning due regard to the Judaic background enveloping Aksumite religion and antiquity. This attempt adds to the development of an integrated approach to church history, where the integrated narrative of Aksumite Christianity will be composite to the complete documentation of early Christianity. The investigation was accomplished through a multi-approach, whilst the main method was document analysis, as commensurate with the nature of the study, cultural historiography and the archaeology of religion was dually engrained. A review of the conversion and reality of Ezana in tangent with the recorded accounts of Ethiopian Christianity, when exerted through reference to archaeological, epigraphic and numismatic evidence, enhances a comprehensive narrative on the recorded inceptions of Ethiopian Christianity. The conversion of Ezana and the narrative of Frumentius’ ordination as the first Abuna though an account mainly ascribed to narratives by ecclesiastical historians; is an event that can be substantiated through the re-examination of archaeological-epigraphical data. Therefore, Aksumite Christianity should be composite to wholistic Christian narratives as paralleling the manner Vandal episodes and eastern Christianity are duly noted.Intradisciplinary and/or interdisciplinary implications: Whilst the article takes the main form of a historical review of Ethiopian Christianity’s origins, there are inferences to biblical studies and archaeological establishments. The main methodology takes the form of a document analysis in the form of comprehensive literature review which also includes references to epigraphy.